Arizona - Blashfield, Jean F. (New York : Children's Press, 2000)
Describes the geography, plants and animals, history, economy, language, religions, culture and people of the state of Arizona.
Includes bibliographical referenes and index.
Keywords: Arizona -- Juvenile literature